Arrestin domain-containing protein 1-mediated microvesicles (ARMMs) protect against cadmium-induced neurotoxicity - Zunwei Chen; Zhi Qiao; Charlotte R. Wirth; Hae-Ryung Park; Quan Lu (Extracellular Vesicle)
Exposure to environmental heavy metals such as cadmium (Cd) is often linked to neurotoxicity but the underlying mechanisms remain poorly understood. Here we show that Arrestin domain-containing protein 1 (ARRDC1)-mediated microvesicles (ARMMs)–an important class of extracellular vesicles (EVs) whose biogenesis occurs at the plasma membrane–protect against Cd-induced neurotoxicity. Cd increased the production of EVs, including ARMMs, in a human neural progenitor cell line, ReNcell CX (ReN) cells. ReN cells that lack ARMMs production as a result of CRISPR-mediated ARRDC1 knockout were more susceptible to Cd toxicity as evidenced by increased LDH production as well as elevated level of oxidative stress markers. Importantly, adding ARMMs back to the ARRDC1-knockout ReN cells significantly reduced Cd-induced toxicity. Consistent with this finding, proteomics data showed that anti-oxidative stress proteins are enriched in ARMMs secreted from ReN cells. Together our study reveals a novel protective role of ARMMs in Cd neurotoxicity and suggests that ARMMs may be used therapeutically to reduce neurotoxicity caused by exposure to Cd and potentially other metal toxicants.